Fabrication of Cu2SnS3 thin film solar cells by sulphurization of sequentially sputtered Sn/CuSn metallic stacked precursors - Hossain E.S.; Chelvanathan P.; Shahahmadi S.A.; Bais B.; Akhtaruzzaman M.; Tiong S.K.; Sopian K.; Amin N. (Elsevier Ltd, 2023)
Copper compounds; Copper metallography; Deposition; Efficiency; Energy gap; Fabrication; IV-VI semiconductors; Layered semiconductors; Metals; Solar power generation; Thin film solar cells; Thin films; Tin metallography; Fabrication technique; Microstructural degradation; P type conductivity; Photovoltaic devices; Photovoltaic technology; Polycrystalline film; Secondary phase; Thin-film depositions; Tin compounds; correlation; decomposition; degradation; efficiency measurement; electronic equipment; equipment; film; fuel cell; inorganic compound; performance assessment; photovoltaic system; technological change